2020
DOI: 10.1177/0963689720965178
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Identification of Potential Hub Genes in Muscle-Invasive Bladder Urothelial Carcinoma

Abstract: Despite aggressive treatment approaches, muscle-invasive bladder urothelial carcinoma (MIBC) patients still have a 50% chance of developing general incurable metastases. Therefore, there is an urgent need for candidate markers to enhance diagnosis and generate effective treatments for this disease. We evaluated four mRNA microarray datasets to find differences between non-MIBC (NMIBC) and MIBC tissues. Through a gene expression profile analysis via the Gene Expression Omnibus database, we identified 56 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…While Su et al indicated that let-7d can at least partially inhibit growth, metastasis, and tumor macrophage in ltration in renal cell carcinoma by targeting COL3A1 and CCL7 [42]. Yuan et al discovered that COL3A1 played certain roles in the progression of human UC and in uenced the prognosis probably by regulating MAPK signaling pathway, which contributed to the poor prognosis of UC [42]. These were consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…While Su et al indicated that let-7d can at least partially inhibit growth, metastasis, and tumor macrophage in ltration in renal cell carcinoma by targeting COL3A1 and CCL7 [42]. Yuan et al discovered that COL3A1 played certain roles in the progression of human UC and in uenced the prognosis probably by regulating MAPK signaling pathway, which contributed to the poor prognosis of UC [42]. These were consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…These were consistent with our results. In a previous study, the in situ expression of COL5A2 increased in invasive breast cancer and was associated with ECM remodeling, suggesting that COL5A2 is associated with tumor progression in breast cancer [42]. Moreover, the expression of COL5A2 was related to the malignancy of colorectal cancer, suggesting its potential as a biomarker for colorectal cancer.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations